A percepção dos professores do Curso de Medicina da Universidade Federal de Minas Gerais em relação ao sofrimento psíquico de seus alunos - Maria Aparecida Miranda da Silva (2016)
Introduction: Psychological distress of medical students is known. The role of the teaching staff in detecting the difficulties causing students psychological distress and knowledge about handle them is fundamental to prevent the problem. However, medical teachers are not always prepared to deal with these challenges. Objective: To study the perceptions of the teaching staff of the medical school at Universidade Federal de Minas Gerais (FMUFMG) concerning the psychologicaldistress of the students. The aim of the study was also to assess if they consider it as the task of the professor to care for this suffering and to verify whether they are aware of the psycho-pedagogical support programs meant for the student. Method: A crosssectional quantitative study carried out with the teaching staff of the professional level of the medical school at UFMG. The sample of 102 teachers was obtained by random draw and divided by four groups: male up to ten (10) years of teaching, male with more than ten (10) years, female up to ten (10) years of teaching, and female with more than ten (10)years. A self-applied 28-item questionnaire which uses a 5-point Likert scale from strongly agree to strongly disagree was prepared. For data analysis fourindicators were elaborated: psychological distress perception indicator (IPSP), commitment of the teacher to the student emotional difficulties indicator (ICDE), performance in the face of psychological distress indicator (IAPS) and a general indicator (IG). The quartile analysis was carried out and the difference among the groups was calculated using nonparametric tests. Five questions that were not included in the indicators had an independent analysis. Results: Seventy nineteachers have participated, while 07 out of 102 teachers have refused to participate. Varying teaching staff concern between the groups related to the psychological distress of the students has been shown. For the IG, the female teachers with a longer teaching experience have obtained a higher median in relation to the men with less teaching experience. (p<0,05). For the others indicators, despite the difference between the quartiles, the comparison of the medians has not shown statisticallysignificant differences. It was not possible to answer if the teaching staff consider the care of students psychological distress as a task of the professor. 16,5% of th teachers do not know the psychological support programs aimed to the students. The results show that from the total of teachers, 85% have already met students with emotional difficulties. Men have stated, more frequently, that they ignored the existence of emotional problems among the students. More than 50% of the teaching staff have not noticed the occurrence of bullying at FMUFMG. For acts or attitudestriggering psychological distress in students, only 28% of the whole group has responded affirmatively. Of the total of respondents, 75, 9% would like to have a emotional support programs tended to help the teacher. Final considerations: Th present study, despite the limitations, is unique in assessing the perception of the teaching staff of the medical school concerning the psychological distress of the students. Teaching experience time and female status seems to play an important rolein the perception of the teaching staff of student psychological distress. A significant portion of the teaching staff ignores the existence of psychological support programs to the students. Bullying and harassment situations at the medical school are denied by many teachers.